Understanding the Money-Sign and How Interpretation Goes Wrong. Issue 4 (2nd October 2022) - Matthews, Nicola R.
Abstract: Money is something apparently known by most everyone living in exchange-dominated economies. When queried exactly what is known about it, the common response is that it is a "thing" of great worth. Implied in the notion of describing it as a "thing" rather than a piece of paper is that it must exhibit some additional abstract feature. What exactly this feature is however remains largely shrouded to many. Despite the more recent and clarifying work of Modern Monetary Theory economists explaining not only what money is but also how it operates, effectively conveying this empirically based theory to the broader public has proven to be more difficult. This paper attempts to identify the problems associated with explaining money to an audience already thoroughly familiar with the topic. Charles S. Peirce's theory of signs will be used to reconstruct money's abstract character and make visible the unknowns of money's supposed "known-ness."